UPAYA MENINGKATKAN MINAT BELAJAR MATEMATIKA SISWA DENGAN MENGGUNAKAN PEMBELAJARAN ACTIVE KNOWLEDGE SHARING DI SMA NEGERI 2 SIABU - Alhadi Siregar; Benny Sofyan Samosir; Lisna Agustina (Jurnal Karya Pendidikan Matematika, 2020)
The purpose of this study was to increase students' interest in learning mathematics by using Active Knowledge Sharing learning on the subject matter of the composition of two functions and inverses of a function. This research is classroom action research (CAR). The subjects in this study were students of class XI IPA 2 Siabu High School consisting of 16 female students and 5 male students. The results of the study after using Active Knowledge Sharing learning were seen in the results of the questionnaire interest in mathematics learning for students in cycle I with an average of 60,23% while the average cycle II was 81,78%. Judging from the results of the cycle I mathematics learning test with a percentage of completeness of 38,10% while the second cycle the percentage of completeness was 85,71%. The results of the observations of student activities in the first cycle averaged 76,15% while the average cycle II was 89,80%. From the results of this study it can be concluded that using Active Knowledge Sharing learning can increase students' interest in learning mathematics in SMA 2 Siabu on the subject of the composition of two functions and the inverse of a function.